Analisis Senyawa Aktif Trigeminal Andaliman dengan Variasi Metode Pengeringan dengan Pendekatan GC-MS - Sigit Suharta; Dase Hunaefi; Christofora Hanny Wijaya; Yasuyuki Hashidoko (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2022)
Sanshool compounds are the trigeminal active compounds in andaliman (Zanthoxylum acantho-podium DC) with a numbing and tingling sensation. The analysis of such compounds is usually done through HPLC approach; however, limited studies have reported that the analysis of such compounds could be conducted with Gas Chromatography-Mass Spectrometry (GC-MS). This method could save research time and funding by analyzing both sanshools and volatiles simultaneously, which would describe the complete profile of andaliman flavor compounds. This study aimed to confirm the potency of GC-MS in analyzing sanshool compounds and to utilize this method in studying the impact of different drying methods towards andaliman trigeminal active compounds. Andaliman was dried with five drying methods (sun, sunshade, air, oven, and freeze-drying) and was macerated with chloroform, concentrated, and analyzed with GC-MS. The results of this study showed that GC-MS was able to analyze sanshool compounds efficiently. Drying had no statistically significant impact on sanshool quantities extracted from andaliman. Fresh andaliman contained 0.69 % (dry weight basis) of α-sanshool, the main sanshool in andaliman. On the other hand, dried andaliman contained 0.80-1.08% of α-sanshool (dry weight basis). As oven drying managed to produce andaliman with a similar concentration of α-sanshool at a faster time and more affordable cost than other drying methods, oven drying was suggested as the ideal drying method to extend the shelf life of andaliman.